2007
DOI: 10.1016/j.ambp.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Low Parental Literacy Is Associated With Worse Asthma Care Measures in Children

Abstract: Objective-To determine if parental literacy is related to emergency department visits, hospitalizations, and days of school missed for children with asthma.Methods-We performed a retrospective cohort study at a university pediatric clinic. We enrolled children between 3 and 12 years old with a diagnosis of asthma and a regular source of care at the site of the study and their parent or guardian. Primary asthma care measures included self-reported rates of emergency department visits, hospitalizations, and days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(220 citation statements)
references
References 32 publications
9
202
3
2
Order By: Relevance
“…Although the 18.5% prevalence rate of low health literacy for the parents in this study falls within the rates of 1-29% reported for a variety of parent samples (DeWalt, Dilling, Rosenthal, & Pignone, 2007;Driessnack, Chung, Perkhounkova, & Hein, 2013;Kumar et al, 2010;Otal et al, 2012;Wittich, Mangan, Grad, Wang, & Gerald, 2007;Yin et al, 2009), it is lower than the 28.7% prevalence rate reported for a national sample of parents (Yin et al, 2009). Although no longitudinal data have been reported examining the change in health literacy level after the diagnosis of diabetes, it is plausible that parents, experienced in the health care demands of caring for a child with type 1 diabetes, may have improved health literacy.…”
Section: Prevalence Of Low Health Literacysupporting
confidence: 65%
See 2 more Smart Citations
“…Although the 18.5% prevalence rate of low health literacy for the parents in this study falls within the rates of 1-29% reported for a variety of parent samples (DeWalt, Dilling, Rosenthal, & Pignone, 2007;Driessnack, Chung, Perkhounkova, & Hein, 2013;Kumar et al, 2010;Otal et al, 2012;Wittich, Mangan, Grad, Wang, & Gerald, 2007;Yin et al, 2009), it is lower than the 28.7% prevalence rate reported for a national sample of parents (Yin et al, 2009). Although no longitudinal data have been reported examining the change in health literacy level after the diagnosis of diabetes, it is plausible that parents, experienced in the health care demands of caring for a child with type 1 diabetes, may have improved health literacy.…”
Section: Prevalence Of Low Health Literacysupporting
confidence: 65%
“…The Rapid Estimate of Adult Literacy in Medicine (REALM) (Murphy, Davis, Long, Jackson, & Decker, 1993) is the most commonly used instrument in health literacy research and has been used to measure parent health literacy (DeWalt, Dilling, Rosenthal, & Pignone, 2007;Yin, Dreyer, Foltin, van Schaick, & Mendelsohn, 2007). The REALM focuses on basic reading and writing skills, measuring functional health literacy.…”
Section: Measurement Of Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…DeWalt et al found that parent health literacy was associated with ED visits, hospitalizations, and missed school days among inner-city children with asthma. 29 Shone et al found similar findings for healthcare use. 31 In contrast, we did not find these relationships, similar to findings in urban upstate New York 31 and Midwestern urban African American 32 cohorts.…”
Section: Discussionmentioning
confidence: 74%
“…27,28 Findings for pediatric asthma outcomes are inconsistent. Lower parent health literacy has been associated with more healthcare utilization by children with asthma in some studies, 29,30 but not in others. 31,32 Two studies examining parent health literacy and child asthma control have disparate findings: one reports an indirect relationship between health literacy and asthma control through satisfaction with shared decision making, 33 while the other found no relationship.…”
Section: Introductionmentioning
confidence: 93%